Food Consumption in the City Practices and patterns in urban Asia and the Pacific - Sahakian, Marlyne; Saloma, Czarina; Erkman, Suren (Routledge Studies in Food, Society and the Environment, 2016)
Food consumption patterns and practices are rapidly changing in Asia and the Pacific, and nowhere are these changes more striking than in urban areas. This book brings together scholars from anthropology, sociology, environmental studies, tourism, architecture and development studies to provide a comprehensive examination of food consumption trends in the cities of Asia and the Pacific, including household food consumption, eating out and food waste. The chapters cover different scales of analysis, from household research to national data, and combine different methodologies and approaches, from quantifiable data that show how much people consume to qualitative findings that reveal how and why consumption takes place in urban settings. Detailed case studies are included from China, India, Japan, Malaysia, Philippines, South Korea and Vietnam, as well as Hawai'i and Australia. The book makes a timely contribution to current debates on the challenges and opportunities for socially just and environmentally sound food consumption in urbanizing Asia and the Pacific. Chapter 3 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138120617_oachapter3.pdf